Human capital and economic growth: a review essay - Marinko Škare; Sabina Lacmanović (Amfiteatru Economic Journal, 2015)
Human capital as a critical engine of economic growth is present in many empirical and theoretical body of knowledge on growth models and theory. However, the conclusion on its importance as a driver of economic growth remains inconclusive. The aim of this study is to provide and detailed overview on theoretical and empirical research investigating the role of human capital in the economic growth phenomena. Measuring human capital remains the main obstacle to assessing the importance of human capital and education in economic growth. The time lag present causes additional restrictions in the schooling process itself which in the today dynamic and globalized world present a real obstacle to measuring human capital role in growth models. Costs principle in measuring human capital proxy may not be a best approach to use in growth accounting models. Other not quantitative (subjective) factors affect human capital to a degree not less than quantitative are like motivation, commitment, vision. These factors have to be accounted for if an adequate fit for proxy of human capital in growth models in future prospective research on endogenous growth models and theories.
Keywords: E24; J24; O15; O40; 330; schooling; growth; human capital; growth models; knowledge economy